Job Satisfaction and Quality of Work Life As a Commercial Flight Crew – A Review - Mat Tiya, Farah Azwa; Mohd Yunos, Siti Nur Mariani (Progress in Aerospace and Aviation Technology, 2021)
The rapid growth of aviation industry resulted in a growing pilot demand globally from year to year. The increasing rate of pilot employed triggers all airliners to meet the needs of the organization that affect job satisfaction. Now, much attention has been given to the issue regarding quality of work life as flight crew by the management in the aviation sector as it is pertains to employee behaviour. Job satisfaction of flight crew describe on how well the job provides fulfilment and it serves as a source or means of enjoyment to every flight crew. Job satisfaction is important as it represent the degree to which flight crew feel positively or negatively about their job. There are many studies conducted to show the level of working satisfaction. However, not many studies have clearly demonstrated and discussed the quality of work life as a flight crew working in aviation industry. Therefore, this study aims to highlight the quality of work life as a flight crew working in aviation industry. All data from books, journal and articles were analysed. The result revealed that the job meaningfulness factor has the greatest impact on job satisfaction among flight crew working with commercial airlines in aviation industry. On the other hand, the lowest satisfied aspect among flight crew is related to reward and fairness aspect.